Diversity amongst human cortical pyramidal neurons revealed via their sag currents and frequency preferences - Homeira Moradi Chameh (Nature Portfolio, 2021)
The unique biophysical properties of human cortical neurons that may underlie interlaminar communication are explored. With a focus on I h and layers 2&3, 3c, and 5, the authors show that L5 pyramidal neurons are better adapted than their superficial layer counterparts to track delta and theta frequency inputs.